Contemporary sport management - Pedersen, Paul M. (Human Kinetics, 2011)
This book provides students with an overview of sport management by presenting extensive discussions of the foundational aspects of the profession and current topics from the field. Students will learn the relevance of sociological, cultural, historical, political, psychological, and legal concepts to the management of sport; the necessary professional skills and attitudes of sport managers; and ways in which the globalization of sport continues to affect sport management professions.--[book cover]